Modulating effects of bioactive water Naftussya from layers Truskavets’ and Pomyarky on some metabolic and biophysic parameters at humans with dysfunction of neuro-endocrine-immune complex - Gozhenko, Anatoliy I; Sydoruk, Nadiya O; Babelyuk, Valeriy Ye; Dubkova, Galyna I; Flyunt, Viktor R; Hubyts’kyi, Viktor Yo; Zukow, Walery; Barylyak, Liliya G; Popovych, Igor L. (Journal of Education, Health and Sport, 2016)
Background. Previously we have been carry out comparative investigation immediate effects of Bioactive Water Naftussya from layers Truskavets’, Pomyarky and Skhidnyts’a on neuro-endocrine-immune complex at men with its dysfunction. The aim of this study is the influence of the use of the course of Bioactive Water Naftussya from layers Truskavets’ and Pomyarky on some metabolic and biophysical parameters at similar patients. Materials and methods. The object of observation were 20 volunteers: ten women and ten men aged 33-76 years without clinical diagnose but with dysfunction of neuro-endocrine-immune complex and metabolism. In daily urine and venous blood we determined the content of electrolytes, nitrogenous metabolites and lipids, recorded conductivity of acupuncture points, rate of electronegative nuclei of buccal epithelium as well as parameters of gas discharge vizualisation (GDV). After examination volunteers within 7 days used bioactive water Naftussya (250 mL three times a day) from Truskavets’ or Pomyarky layer, then repeated the tests listed. Results. Weekly use of Bioactive Water Naftussya increases in the normal level of plasma chloride and sodium, normalizes low level of bicarbonate and decreases within the normal levels of potassium and phosphate. Urinary excretion of sodium and chloride increases while excretion and concentration of uric acid decreases, as the urine concentration of phosphates. The index lithogenicity urine decreased from 112% to 103% norm standard. Initially reduced level of plasma triacylglycerides increases, while decreases in the normal level of cholesterol in low-density lipoprotein composition. Among the biophysical parameters detected increase in the normal conductivity acupuncture points Pg (ND) at right side, which represent the nervous system, and left shift the ratio between the conductivity of acupuncture points MC (AVL), which represents the immune system. Increases electrokinetic index of epithelial cells of cheek to 1,7±0,3%, that indicating the "rejuvenation" of the organism to 1,4±0,3 years. We first discovered changes in parameters of GDV, namely elimination of asymmetries of virtual chakras (first, second and third) as well as reducing the excess energy of the first chakra. No significant differences between the effects of Bioactive Water Naftussya both fields generally not found. Conclusion. Bioactive water Naftussya both Truskavets’ and Pomyarky layers causes favorable normalizing effects on abnormalities parameters of metabolism and gas discharge visualization, which is a manifestation of its adaptogenic properties.